2017
DOI: 10.3389/fnana.2017.00024
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Neurogenesis and Identification of Neuronal Progenitor Subtypes during Pallial Development in Xenopus laevis

Abstract: The complexity of the pallium during evolution has increased dramatically in many different respects. The highest level of complexity is found in mammals, where most of the pallium (cortex) shows a layered organization and neurons are generated during development following an inside-out order, a sequence not observed in other amniotes (birds and reptiles). Species-differences may be related to major neurogenetic events, from the neural progenitors that divide and produce all pallial cells. In mammals, two main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 114 publications
(203 reference statements)
6
52
0
Order By: Relevance
“…Another interesting observation of the present study is that the cell layers of the lizard lcs appear to originate following an inside‐out pattern (as explained in the Results section): that is, based on the first visualization and relative position of these Lhx9‐expressing layers during development, the deep layer (DC3) appears to be formed earlier than the superficial layer (LCd). If confirmed by experimental neurogenesis studies (using BrdU or other markers of neurogenesis), this would be the first evidence for an inside‐out pattern of pallial layer formation (or cell aggregation) in reptiles, in which the outside‐in pattern is the general rule and this is considered to be the ancestral condition in tetrapods (Goffinet, ; Medina & Abellán, ; Moreno & González, ). In contrast, in the mammalian pallium, the prevalent temporal order of layer formation follows a birthdate‐dependent inside‐out pattern, which is observed in the neocortex and the entorhinal cortex, but—in contrast to previous suggestions—this pattern is absent or less clear in hippocampal formation subdivisions as the subiculum (Wyss, Sripanidkulchai, & Hickey, ), the CA fields and the dentate gyrus (Hayashi, Kubo, Kitazawa, & Nakajima, ; Xu et al, ).…”
Section: Discussionmentioning
confidence: 67%
“…Another interesting observation of the present study is that the cell layers of the lizard lcs appear to originate following an inside‐out pattern (as explained in the Results section): that is, based on the first visualization and relative position of these Lhx9‐expressing layers during development, the deep layer (DC3) appears to be formed earlier than the superficial layer (LCd). If confirmed by experimental neurogenesis studies (using BrdU or other markers of neurogenesis), this would be the first evidence for an inside‐out pattern of pallial layer formation (or cell aggregation) in reptiles, in which the outside‐in pattern is the general rule and this is considered to be the ancestral condition in tetrapods (Goffinet, ; Medina & Abellán, ; Moreno & González, ). In contrast, in the mammalian pallium, the prevalent temporal order of layer formation follows a birthdate‐dependent inside‐out pattern, which is observed in the neocortex and the entorhinal cortex, but—in contrast to previous suggestions—this pattern is absent or less clear in hippocampal formation subdivisions as the subiculum (Wyss, Sripanidkulchai, & Hickey, ), the CA fields and the dentate gyrus (Hayashi, Kubo, Kitazawa, & Nakajima, ; Xu et al, ).…”
Section: Discussionmentioning
confidence: 67%
“…These features resemble bRGCs in the OSVZ, which are abundant in the developing carnivore and primate neocortex (Fietz et al 2010;Hansen et al 2010;Reillo et al 2011;Dehay et al 2015). The existence of basal mitotic cells in the developing amphibian pallium suggested that vestigial population of basal progenitors already evolved in pre-amniote animals (Nomura et al 2016;Moreno & Gonzalez 2017). Of note, most of basal mitotic cells in the amphibian and avian pallium are negative for Tbr2 ( Fig.…”
Section: Neurogenesis In Avian Palliummentioning
confidence: 85%
“…The existence of basal mitotic cells in the developing amphibian pallium suggested that vestigial population of basal progenitors already evolved in pre‐amniote animals (Nomura et al . ; Moreno & Gonzalez ). Of note, most of basal mitotic cells in the amphibian and avian pallium are negative for Tbr2 (Fig.…”
Section: Neurogenesis In Avian Palliummentioning
confidence: 98%
“…Imaging at subsequent timepoints showed neurites extending out from the VZs (Figure 6B and Video 7). These features closely resemble neurogenesis in the developing neural tube and telencephalon in vivo (Graham et al, 2003;Moreno and González, 2017), as well as cortical organoids generated by PSC differentiations in 3D droplets (Lancaster et al, 2013;Pașca et al, 2019), suggesting monolayer differentiations also result in the formation of complex cortical structures. Immunostaining at Day 54 confirmed the NPC identity of the radially aligned cells persisted in the VZs, staining positive for Sox2 and Pax6 (Figures S6A and S6B).…”
Section: Resultsmentioning
confidence: 57%
“…Immunostaining at Day 54 confirmed the NPC identity of the radially aligned cells persisted in the VZs, staining positive for Sox2 and Pax6 (Figures S6A and S6B). Analysis of the rainbow reporter and neurite markers at day 54 demonstrated that NPCs in VZs generated neurons expressing the same color barcode, with newborn DCX + neurons residing proximal to the VZ and MAP2 + terminally differentiated neurons localizing more distal to the VZ (Figures 6B, 6C and S6A), consistent with neurogenesis in vivo (Moreno and González, 2017;Johnson et al, 2018). Co-staining of Pax6 and TBR1 (Figure S6C) confirmed the self-organized spatial patterning of NPCs and postmitotic cortical projection neurons in vitro were consistent with mammalian corticogenesis in vivo (Englund et al, 2005;Bedogni et al, 2010).…”
Section: Resultsmentioning
confidence: 63%